2019
DOI: 10.15324/kjcls.2019.51.3.329
|View full text |Cite
|
Sign up to set email alerts
|

Laboratory Investigation of Human Rhinovirus Infection in Cheonan, Korea

Abstract: Annually, millions of children die from respiratory virus infections. Human rhinovirus (HRV) is a causative agent of severe respiratory infections in young, elderly, and asthmatic patients with weak immunity. In this study, 9,010 respiratory virus specimens were collected from January 2012 to December 2018 at Dankook University Hospital, Cheonan and examined by real-time reverse transcription polymerase chain reaction. Twelve respiratory viruses were detected. The mean detection rate was 21.3% (N=1,920/9,010),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 21 publications
2
0
0
Order By: Relevance
“…These results may be due to the fact that HRV infections are more severe in winter and more hospitalizations occur during this season. Although all age groups were included, children aged between 2-<5 years showed a higher rate of HRV infection (21%), which was reported in previous studies (13). Our results, in line with previous reports, indicated that the detection rates gradually decrease with patient age (13,14).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…These results may be due to the fact that HRV infections are more severe in winter and more hospitalizations occur during this season. Although all age groups were included, children aged between 2-<5 years showed a higher rate of HRV infection (21%), which was reported in previous studies (13). Our results, in line with previous reports, indicated that the detection rates gradually decrease with patient age (13,14).…”
Section: Discussionsupporting
confidence: 91%
“…Although all age groups were included, children aged between 2-<5 years showed a higher rate of HRV infection (21%), which was reported in previous studies (13). Our results, in line with previous reports, indicated that the detection rates gradually decrease with patient age (13,14). As seen in the results, there was no correlation between the disease status (inpatient and outpatient), and the HRV frequency.…”
Section: Discussionsupporting
confidence: 91%